Protection and Promotion of Agricultural and Food Products at European Union level through European Quality Schemes - Laura Cătălina ŢIMIRAŞ (Eastern European Journal of Regional Studies, 2019)
This paper aims to highlight the use of European quality schemes at Community level to protect agri-food products, including alcoholic beverages. After highlighting the advantages granted to products by using these schemes to protect and, implicitly, promote those products having unique characteristics linked to their geographical origin or, as the case may be, the traditional production / processing system, the paper presents the situation at Community level from the point of view of the quantity of products protected through different quality schemes, by country and category of protected products. Among the quality schemes used at EU level for agri-food products, including alcoholic beverages in the present paper we referred to: "geographical indication" and "traditional specialty guaranteed". The paper is based on the information of European Commission in which protected products are registered through different quality schemes, through and the information contained in various scientific papers, normative acts and statistical databases.